Understanding Corporate Green Competitive Advantage through Green Technology Adoption and Green Dynamic Capabilities: Does Green Product Innovation Matter? - Zhu, Yan; Zhang, Huifang; Siddik, Abu Bakkar; Zheng, Yubin; Sobhani, Farid Ahammad (Systems (Basel), 2023)
Our study explores the association between the adoption of green technology and the development of green dynamic capabilities to achieve green competitive advantage. This research concentrates explicitly on the mediating function of green product innovation. The study is grounded in the dynamic capabilities theory and seeks to improve understanding regarding how organizations can attain a competitive edge by employing green practices and capabilities. Data were obtained from 312 manufacturing business managers in Bangladesh. We utilized the partial least squares structural equation modeling (PLS-SEM) method to examine the data and evaluate the proposed hypotheses. The empirical evidence suggests that both green technology adoption and green dynamic capabilities significantly impact firms’ green product innovation and competitive advantage. Additionally, the findings indicate that green product innovation is a mediating variable in the association between green technology adoption-green competitive advantage and green dynamic capabilities-green competitive advantage. This research adds to the current body of literature by presenting empirical findings highlighting the crucial role of green technology and dynamic capabilities in promoting green competitive advantage. Our results reveal that it would be beneficial for organizations to prioritize adopting eco-friendly technologies and cultivating dynamic capabilities to improve their overall green performance. The present study contributes significantly to the literature by offering insights into the strategies managers and policymakers can employ to attain sustainable competitive advantage in the manufacturing sector.